Risiken des Widerstandes : Jugendliche und ihre Rassismuserfahrungen - Scharathow, Wiebke (Kultur und soziale Praxis, 2014)
An insight into the ordinariness of racism: A challenge in the light of restrictive social structures which young people have to meet on a daily basis.